Calcium‐Iron Oxide as Energy Storage Medium in Rechargeable Oxide Batteries. Issue 12 (8th August 2016) - Berger, Cornelius M.; Mahmoud, Abdelfattah; Hermann, Raphaël P.; Braun, Waldemar; Yazhenskikh, Elena; Sohn, Yoo Jung; Menzler, Norbert H.; Guillon, Olivier; Bram, Martin
Abstract : Rechargeable oxide batteries (ROB) comprise a regenerative solid oxide cell (rSOC) and a storage medium for oxygen ions. A sealed ROB avoids pumping loss, heat loss, and gas purity expenses in comparison with conventional rSOC. However, the iron oxide base storage medium degrades during charging–discharging cycles. In comparison, CaFe3 O5 has improved cyclability and a high reversible oxygen storage capacity of 22.3 mol%. In this study, we analyzed the redox mechanism of this compound. After a solid‐state synthesis of CaFe3 O5, we verified the phase composition and studied the redox reaction by means of X‐ray diffraction, Mössbauer spectrometry, and scanning electron microscopy. Results show a great potential to operate the battery with this storage material during multiple charging–discharging cycles.